Towards development of personalized implants with antibacterial bioactive coating by the selective laser melting and RF magnetron sputtering methods - Prosolov K. A. Konstantin Alexandrovich; Khimich M. A.; Ibragimov E. A. Egor Arturovich; Kovalevskaya Zh. G. Zhanna Gennadievna; Saprykin A. A. Aleksandr Aleksandrovich; Sharkeev Yu. P. Yury Petrovich (2018, 2018)
Заглавие с экрана